IIUM headmaster's experiences of ETeMs: its implementations and challenges. - Hussien, Suhailah; Nik Abd. Rahman, Nik Suryani (s.n, 2012)
The study conducted is aimed to examine the perception of selected primary school headmasters regarding the implementation of English Teaching for Mathematics and Science (ETeMS. The purpose of the study is to explore and understand how the schools in general and the headmaster/mistress in particular, implement ETeMS and manage its problems and challenges. It is hoped that the study would be able to inform the Ministry of Education the extent of the implementation of ETeMS and the impact of ETeMS and revert policy on the schools.